Switching Modulation Strategies for Multilevel Inverter (ELEKTRIKA- Journal of Electrical Engineering, 2021)
There is always a need to create efficient and optimized converters to deliver the best possible results to achieve a better THD profile in the waveform output. One way is by controlling the switching of the power switches of the converters using appropriate modulation schemes. While numerous works have been done in proposing new switching modulation strategies for multilevel inverters, this work will compare multicarrier PWM and near-to-level control (NLC) modulation schemes. In this paper, multicarrier PWM variants, namely, PD-PWM, POD-PWM, and APOD-PWM, are designed and simulated. Their voltage THD and spectrum performance are discussed when applied to single-phase 7, 9, and 11-level cascaded multilevel inverters. Then NLC modulation will be designed and applied to similar multilevel inverter circuits. It will be shown that the NLC exhibits some superior performances compared to PWM-based but with several drawbacks that can be optimized.